Upotreba jezika etničkih zajednica u MRTV-u - Donev, Dejan; Petroska, Paraškeva (Akademija društvenih nauka, Bijelo Polje, 2015)
The media space in Republic of Macedonia is already shaped and distributed. It is composed of public broadcasting and commercial broadcasting, i.e. dual media system, by which the functions of the public broadcaster service performs Macedonian Radio Television (MRT), which operates in the manner and conditions stipulated by the Law on Broadcasting (“Official Gazette” no. 100/2005 and 19/2007). In the media sector in Macedonia, minority ethnic communities have a constitutionally guaranteed right to freedom of expression under the Article 48 of the Constitution, and also by the first Broadcasting Act passed in 1997, according to which on the members of nationalities the right to free express, foster and develop their identity and national characteristics is guaranteed. The author in the text treats the problem of the actual ways on which the languages of ethnic communities in Republic of Macedonia are set in the media space, because the Macedonian Television as a public service beside having the obligation to service all citizens on their native languages, for now it only coveres those citizens who are included in the Preamble of the Constitution, which means nonrespecting the principle of equal (balanced) representation of programs on the languages of ethnic communities in its program.
The Usage of Languages of Ethnic Communities in MRTV
Keywords: public service, ethnic community, language, right of expression